Kebutuhan Spiritual pada Pasien Kanker Stadium Lanjut - Indra, Ibaadi; Afiyanti, Yati; Hargiana, Giur (Journal of Telenursing (JOTING), 2024)
This study aimed to determine the various spiritual needs of patients with advanced cancer. The method used was a systematic review with article searches in nine journal databases, such as PubMed, Scopus, EBSCOhost, ClinicalKey Nursing, SpringerLink, PMC, Sage Journal, ProQuest, and ScienceDirect. Article analysis used the PRISMA method. The results showed that there were six articles that met the criteria that discussed spiritual needs in advanced cancer patients. All articles used quantitative research methods with a cross-sectional design. In conclusion, spiritual needs in advanced cancer patients can include the need for connection, peace, meaning or purpose, and transcendence. Meeting spiritual needs through holistic nursing care can help patients reduce suffering. Keywords: Advanced Cancer, Spiritual Needs